Application of Lean methodologies in the reduction of setup times in the pharmaceutical industry - André Gil Curado; António Abreu (Instituto Politécnico de Viseu, 2019)
Introduction: The strong international competitiveness motivated by globalization with the purpose of reaching an increasingly demanding public, makes cost reduction and quality increase a primary need across all sectors. The generic drug industry where price is the primary weapon in consumer reach is no exception and creates a strong need in the application of Lean methodologies to optimize the production. Objectives: Reduce of changeover times by the application of lean methodologies structured by a proposed model. Methods: This study started with a review of the bibliography of the Lean's origin and the several methodologies ending with the application of a proposed application model. The implementation was based on a detailed study of the setups resulting in a set of solution proposals dedicated to the main problems applying several lean tools. Results: Reduction of change times by 20% and waiting times by 24.5% within 3 months. Conclusions: The application of Lean methodologies revealed a great utility in the identification of causes and in the creation of solutions. The implementation of this model, although in an initial phase, allowed not only reduction of the times of changes, but also other improvements such as the reduction of the number of waits. However, this application, due to being inserted in the pharmaceutical industry, is limited by some procedures that cannot be changed.